Utility of Adipocyte Fractions in Fat Grafting in an Athymic Rat Model. (2nd May 2018) - Akgul, Yucel; Constantine, Ryan; Bartels, Mason; Scherer, Philipp; Davis, Kathryn; Kenkel, Jeffrey M
Abstract: Background: Multiple processing and handling methods of autologous fat yield to variations in graft retention and viability, which results in unpredictable clinical outcomes. Objectives: This study aims to understand the skin effects of fat graft preparations that contain a varying ratio of free-lipid and stem-cell-bearing stromal vascular fractions (SVF). Methods: Lipoaspirates from consenting patients were processed into emulsified fat and then SVF and adipocyte fractions (free-lipid). SVF enriched with 0%, 5%, and 15% free-lipid were grafted along the dorsum of athymic rats. The xenografts were collected 45 days after grafting and then prepped for immunostaining. Results: Xenografts resulted in viable tissue mass under the panniculus carnosus of rats as confirmed with human specific markers. A low percentage of human cells was also detected in the lower reticular dermis. Although grafts with SVF formed adipocytes of normal architecture, grafts formed with free-lipid alone resulted in large lipid vacuoles in varying sizes. Among graft preparations, SVF with 10% free-lipid resulted in much-developed adipocyte architecture with collagen and elastin. Compared with SVF alone grafts, SVF with free-lipid had higher CD44 expression, suggesting a localized immune response of adipocytes. Conclusions: Current studies suggest that SVF enriched with approximately 10% free-lipid provides the best conditions for fat graft differentiation into viable fat tissue formation as well as collagen and elastin production to provide mechanical support for overlaying skin in an athymic rat model. Additionally, application of this therapeutic modality in a simple clinical setting may offer a practical way to concentrate SVF with free-lipid in a small volume for the improvement of clinical defects. Level of Evidence: 5: